The Accounting Irregularities, Transfer Pricing Aggresiveness, and Firm Value: Does Tax Aggressiveness Matter? - Wardhana, Rony; Anam, Saiful; Ivanda, Muhammad Nur Miftakhul; Tjaraka, Heru; Hidayatullah, Hidayatullah (AKRUAL: JURNAL AKUNTANSI, 2024)
Introduction / Main Objectives: This research aims to examine factors that influence firm value, including Accounting Irregularities, Tax Aggressiveness, Transfer Pricing Aggressiveness. Background Problems: The company has the aim of getting profits that continue to grow consistently to increase firm value. Research Method: The notion was tested using Smart Partial Least Square (SmartPLS) version 3.0 software. Numeric data used in the computations is derived from secondary sources. This study focuses on the examination of financial data pertaining to manufacturing enterprises throughout the time frame of 2016 to 2022. Findings / Results: The findings of this study are that Accounting Irregularities and Transfer Pricing Aggressiveness have an effect on Tax Aggressiveness, but Accounting Irregularities, Transfer Pricing Aggressiveness and Tax Aggressiveness have no effect on Firm value. Mediation one and mediation two in this study also had no effect. Conclusion: These results can be a reference for investors in making investment decisions, companies in making decisions regarding tax avoidance can also use this research as a reference. The novelty of this research is the Accounting Irregularities variable with the mediation of tax aggressiveness on firm value, which has not been studied much in previous research.